Analysis of the Compensation Mechanisms for Ecosystem Services. Case: Sanitation Service Providers - Miranda Quispe, Diana Alexandra (2021)
This article presents the findings obtained from the study on remuneration mechanisms for ecosystem services (MRSE), based on payments for ecosystem services that are implemented in Peru, intending to analyze how they can be applied by the provider companies of the country to ensure the permanence of benefits generated by ecosystems. The methodological approach used to analyze and detail how the implementation of the MRSE occurs and the channeling of the economic resources of these was of a qualitative descriptive type, based on the information obtained from the related documentary records of the years 2013-2019 with the water utilities that made up the sample and the interview of the actors of these companies, who were selected through an intentional-stratified sampling. The results showed that, although the water utilities have made progress in the MRSE implementation process, it requires some adjustments to be able to fulfill its purpose of ensuring the permanence of the benefits generated by the ecosystems. This study allowed to conclude that the process for channeling financial resources through the water utilities can be shortened because it does not depend on the fulfillment of all the stages of the MRSE implementation process. In addition, a baseline is required to provide more information about the results and impact of MRSE interventions, and monitoring is required to demonstrate conclusive results on these.